Representasi nilai pendidikan dalam upacara perkawinan masyarakat suku Pamona - Yunidar Yunidar (Universitas Mulawarman, 2023)
The Pamona tribe's traditional marriage ceremony, called mangawianaka ada mporongo malulu ada pamona (performing a marriage that follows Pamona customs), is led directly by the customary chief and the Pamona tribal customary council. The Pamona tribe's traditional marriage ceremony consists of several requirements that must be prepared and fulfilled by both parties of the prospective bride and groom to get goodness in the future. This research aims to reveal the educational values of the Pamona tribe's marriage customs from the perspective of the Sociology of Literature. The type of research used is qualitative research with a descriptive approach method that describes or paints symptoms and facts systematically. The data collection technique used listening to recordings of informant interviews, field notes, and other literature sources. Based on the results of the research, the educational values contained in the expression of the Pamona tribe's traditional marriage consist of (1) religious values, (2) moral values, (3) social values (4) and cultural values. The educational values revealed in the Pamona tribe's traditional marriage are not only in the form of educational values but also represent social values in the Pamona tribe community.